Identification of a Functional Epitope in Plasminogen Activator Inhibitor-1, not Localized in the Reactive Center Loop - Debrock, Sophie; Declerck, Paul J. (Thrombosis and Haemostasis, 1998)
Plasminogen activator inhibitor-1 (PAI-1) is unique among the ser-pins because of its conformational flexibility. Previously, we have characterized monoclonal antibodies that neutralize PAI-1 activity by switching the active, inhibitory pathway into the non-inhibitory substrate pathway (10). Here, we report the identification of the epitopes for two of these antibodies, i.e. MA-55F4C12 and MA-33H1 and apply this information to explain their functional effects.Using a random PAI-1 epitope library (11), phages displaying specific PAI-1 fragments were isolated after selective screening for binding onto the respective antibodies. Competition experiments with PAI-1 demonstrated that selected phages react with the antigen-binding site of the antibodies. Comparison of the sequences of the different overlapping inserts, encoding the PAI-1 epitope, with the PAI-1 cDNA sequence revealed that both epitopes, even though not identical, are located between amino acids Glu128 and Ala156 in the PAI-1 molecule. Analysis within the three-dimensional structure of PAI-1 showed that these residues completely cover helix F, which is localized close to the major β-sheet A. This localization provides a rational basis for explaining the mechanism of PAI-1 inactivation by both antibodies: upon binding of these antibodies to PAI-1, a stabilizing effect is induced on helix F resulting in a decrease of the kinetics of insertion of the reactive site loop into β-sheet A during interaction with the target proteinase. This forms the molecular basis for the observed functional effects of these antibodies and fully explains why PAI-1, in the presence of these antibodies, has lost its inhibitory properties but remains succeptible to cleavage by its target proteinases. The identification and localization of these functionally important epitopes opens new perspectives for the development of pharmacological agents with PAI-1 modulating properties.